psi(0,1) = w^{e(0)+1}

psi(0,n) = w^{e(0)+n}

psi(0,psi(0)) = w^{e(0)*2}

psi(0,psi(0,psi(0))) = w^w^{e(0)*2}

psi(1,0) = psi(0,W) = e(1)

psi(x,y) = w^{e(x)+y}

psi(0,0,1) = e(0)+1

psi(0,0,n) = e(0)+n

psi(0,0,psi(0)) = e(0)*2

psi(0,0,psi(0,0,psi(0))) = e(0)*3

psi(0,1,0) = psi(0,0,W) = w^{e(0)+1}

psi(0,x,y) = w^{e(0)+x}+y

psi(x,y,z) = w^{e(x)+y}+z

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.